Effect of Permanent Magnet Made by Blocking Magnetization on Magnetic Density and Eddy Current Loss of Permanent Magnet Transmission - Wei Lijun; Wang Jinzhong; Lu Yanghui; Wu Xianfeng; Luo Shuai (Jixie chuandong)
The remanent magnetism hollowing of large permanent magnets has been one of the main obstacles to improve the performance of the permanent magnet transmission with high power and high speed ratio. Compared with the traditional preparation process, blocking magnetization technology can significantly improve the performance of large permanent magnets. A 3D model is constructed to complete the magneto-thermal simulation analysis adopting the difference permanent magnets. The results show that the blocking magnetization process can effectively suppress the hollowing of the magnetic field, significantly improve the remanence of the large-size permanent magnet, and enhance the magnetic density in the permanent magnet gear, resulting in the maximum output torque increase of the permanent magnet gear. The difference between the circumferential arc length, axial length and penetration depth of magnetic field can be reduced obviously by the insulation between blocking magnetizing permanent magnets, and the eddy current loss of the permanent magnet.